Caravanning as a Sustainable Segment of Camping Tourism? Theory and Practice Review - Golub, Barbara; Jaković, Božidar; Kovačević, Martina (Oeconomica Jadertina, 2024)
Ongoing changes within and beyond the tourism market, especially in terms of tourism demand, have led to the emergence and growth of various subcategories and tourism products within camping tourism. One such category is caravanning, which is not only considered a lifestyle but also stands out as a vital segment of camping tourism, significantly shaping, and influencing its sustainability. This paper aims to provide an overview of previous discussions on camping tourism, with a special focus on caravanning as a leading segment within the camping tourism industry, as well as within the broader tourism sector. Moreover, it delves into the sustainability of caravan service providers and the sector. The methodology employed in this paper involves a systematic review of literature from selected databases and other online resources, comprehensively examining relevant studies that explore the caravanning tourism market and the sustainability of camping tourism and caravanning. Alongside the literature review, the paper showcases examples of campsites and caravan parks that prioritize eco-friendly practices. These establishments not only adopt sustainable business strategies such as utilizing recycled and sustainable building materials, reducing paper-based document storage, and embracing eco-friendly products but also focus on conserving energy and water, employing electric transportation, collaborating with local suppliers, implementing waste segregation, promoting traditional vegetation, and advocating for recycling and waste management.